Lethal Concentration 50 (LC50 - 96 hours) Nile Tilapia (Oreochromis niloticus) exposed Cypermethrin-based Pesticide - Yuniari, Shinta Hiflina; Hertika, Asus Maizar Suryanto; Leksono, Amin Setyo (Graduate School, Universitas Brawijaya, 2016)
In aquaculture of an irrigation, the use of cypermethrin-based pesticide can harm nile tilapia which cultured within and its impact on humans who consume the fish. Thus it is necessary to study to determine the threshold of this cypermethrin-based pesticide. Determining the thresholds was using the test of LC50 - 96 hours (Lethal Concentration 50-96 hour) which tested tilapia that dead by 50%, which can be used as a benchmark threshold for cypermethrin-based pesticide. Test of LC50 - 96 hours consist of preliminary test and advanced test. Lethal Concentration 50 (LC50 - 96 hours) of cypermethrin-based pesticide towards nile tilapia (Oreochromis niloticus) is 0.082 ppm. At these doses, tilapia death reached 50%. This concentration is expressed as a threshold usage of cypermethrin-based pesticide on the environment around the aquaculture of tilapia. Keywords: Cypermehrin-based pesticide, LC5096 hour, Nile tilapia.